Design of IoT-Based Temperature Monitoring System for Automated Inhomogeneity Measurement - Saragih, Dearninta A. P.; Tarigan, Kerista; Humaidi, Syahrul; Abdulmajid, Muhammad W.; Santoso, Bayu (Journal of Applied Geospatial Information, 2024)
Badan Meteorologi, Klimatologi, and Geofisika (BMKG): For weather and climate observations, the Meteorology, Climatology, and Geophysics Agency operates 1,285 digital and automated instruments across Indonesia. These instruments need regular calibration as required by Law No. 31 of 2009 on Meteorology, Climatology, and Geophysics. BMKG maintains a calibration laboratorylaboratory in Medan, North Sumatra, complying with ISO/IEC 17025:2017 standards, which ensure the quality of measChamber inhomogeneity, which affects temperature stability, is an important factor in calibration. ibration. To address this, a study designed an IoT-based temperature monitoring system using nine DHT22 sensors to measure chamber temperature inhomogeneity. The IoT system measured an inhomogeneity value of 0.9 0.9 °C, matching standard results using Aqara sensors. The designed system measured inhomogeneity at 0°C through the T6 sensor, while the standard system did so at 2°C with the Aqara 6 sensor, both placed consistently in the upper left rear section. The IoT system improved efficiency, offering real-time monitoring via the ThinkSpeak platform and reducing sampling time to 20 seconds from the standard 30 minutes.